The Influence of Principal Transformational Leadership and Organizational Culture on Teacher Performance in Deep Learning - Nurul Falah Rahmawati; Supandi Supandi; Harjito Harjito (CV. Creative Tugu Pena, 2026)
The Influence of Principal Transformational Leadership and Organizational Culture on Teacher Performance in Deep Learning